Developing an Integrated Energy System Interface for Electricity-Hydrogen Hybrid Nuclear Operations. (December 2020) - Ulrich, Thomas A.; Lew, Roger; Boring, Ronald L.; Mortenson, Torrey; Park, Jooyoung; Medema, Heather
Nuclear power plants are looking towards integrated energy systems to address the challenges faced by increasing competition from renewable energy and cheap natural gas in wholesale electricity markets. Electricity-hydrogen hybrid operations is one potential technology being explored. As part of this investigation a human factors team was integrated into the overall engineering project to develop a human system interface (HSI) for a novel system to extract steam for a coupled hydrogen production process. This paper presents the process used to perform the nuclear specific human factors engineering required to develop the HSI for this novel and unprecedented system. Furthermore, the early integration of the human factors team and the meaningful improvements to the engineering of the system itself in addition to the successful development of the HSI for this particular application are described. Lastly, the HSI developed is presented to demonstrate the culmination of the process and disseminate a potential HSI design for electricity-hydrogen hybrid operations that may be useful for others exploring similar integrated energy systems concepts.